A STUDY ON THE GROWTH OF DIGITAL PAYMENTS IN INDIA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
After the launch of cashless transaction in India, the digital payments or the online payments gradually have been increased and occupied dominant part in money payments. A phenomenal growth has been observed in digital payments in India over the last five years. The digital payments have become an integral part of day-to-day living. The term Digital Payment means making a payment to other person/firm with the help of internet or through electronic mode instead of physical money. The initiative of Digital Payments was taken by Government of India after the announcement of demonetization on 8th November 2016. Through the cashless transactions, the Government of India aimed at ‘empowering the Indian Economy digitally’. India can stand along with the developed countries by empowering the economy digitally. There are various advantages going for digital payments like enhanced security, convenience and accessibility, speed and efficiency, tracking and record-keeping, cost savings, global reach, environmental impact, innovation and integration and trust etc. This paper presents a comprehensive analysis of the growth of digital payments in India. The study analyses the trends and patterns in the adoption of digital payment systems and identifies the key drivers and challenges associated with their growth.